1993
DOI: 10.1172/jci116334
|View full text |Cite
|
Sign up to set email alerts
|

Roles of endothelin-1 and nitric oxide in the mechanism for ethanol-induced vasoconstriction in rat liver.

Abstract: This study was designed to investigate the mechanism for ethanol-induced hepatic vasoconstriction in isolated perfused rat liver. Upon initiation of ethanol infusion into the portal vein at concentrations ranging from 25 to 100 mM, portal pressure began to increase in a concentration-dependent manner and reached maximal levels in 2-5 min (initial phase), followed by a gradual decrease over the period of ethanol infusion (escape phenomenon). Endothelin-1 antiserum significantly inhibited this ethanol-induced he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
76
0
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 30 publications
2
76
0
1
Order By: Relevance
“…[6][7][8]27 Since 1990, the effect of ET-1 on hepatic circulation has been extensively studied using in vivo, ex vivo, or in situ models of rat liver. [27][28][29][30][31][32][33][34][35][36][37] Most studies have shown that ET-1 causes vasoconstriction of the portal vasculatures associated with increased portal pressure. Stellate cells (Ito cells, lipocytes) have gained the greatest attention as the target of ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]27 Since 1990, the effect of ET-1 on hepatic circulation has been extensively studied using in vivo, ex vivo, or in situ models of rat liver. [27][28][29][30][31][32][33][34][35][36][37] Most studies have shown that ET-1 causes vasoconstriction of the portal vasculatures associated with increased portal pressure. Stellate cells (Ito cells, lipocytes) have gained the greatest attention as the target of ET-1.…”
Section: Discussionmentioning
confidence: 99%
“…24 Thus, an imbalance between the vasoconstrictor effects of endothelins and the vasodilator effects of NO may contribute to increased vascular resistance. 25 Both ET-1 and NO are known to regulate vascular tone in the liver 11 and splanchnic circulation; further, nitric oxide regulates endothelin receptors. 26 It is presumed that structural factors are less reversible and result in a more fixed resistance.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It has recently been proposed that hepatic stellate cells play an important role in regulating hepatic sinusoidal tonus and the blood flow under physiological and pathological conditions. [3][4][5][6][7] The contractility of hepatic stellate cells depends on the dynamic control of the balance of two endothelium-derived vasoactive substances, endothelin 1 and nitric oxide (NO). [3][4][5][6][7] Endothelin produces sustained vasoconstriction in the liver, which appears to be related to the contraction of hepatic stellate cells.…”
mentioning
confidence: 99%
“…[3][4][5][6][7] The contractility of hepatic stellate cells depends on the dynamic control of the balance of two endothelium-derived vasoactive substances, endothelin 1 and nitric oxide (NO). [3][4][5][6][7] Endothelin produces sustained vasoconstriction in the liver, which appears to be related to the contraction of hepatic stellate cells. 3,4 In addition, NO is also a potent modulator of stellate cell contractility 5,6 and inhibits the vasoconstriction induced by endothelin in the perfused rat liver.…”
mentioning
confidence: 99%
See 1 more Smart Citation